Microservices architecture in the real world (O'Reilly, 2019)
"Over the past two years, Credit Karma has gone from zero to nearly 100 microservices, supporting over 300 engineers while serving our more than 80 million members. Drawing on his experience at Credit Karma, Mason Jones shares approaches based on his real-world experiences making the shift to microservices, covering routing (How does service A find and call service B?), management (How do you handle hundreds of containers?), observability (How do you know what's going on out there?), and experience (How do your developers deal with these services?), as well as the cultural and organizational impact that you can't avoid. Join in to explore solutions, pitfalls, and practical examples that have worked in the real world at scale. This session was recorded at the 2019 O'Reilly Software Architecture Conference in New York."--Resource description page